2019
DOI: 10.1080/22423982.2019.1583528
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative identification and characterisation of self-reported symptoms arising in humans during experimental exposure to cold air

Abstract: Stenfors (2019) Qualitative identification and characterisation of self-reported symptoms arising in humans during experimental exposure to cold air,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…In particular, short-duration, near-maximal exercise in cold environments and competition-like settings has been linked to a high incidence of EIB during screening of winter athletes (Heir and Larsen 1995 ; Wilber et al 2000 ; Kennedy et al 2019 ). Seasonal increases in airway inflammatory biomarkers have recently been highlighted in winter endurance athletes without asthma (Kennedy et al 2016 ; Kurowski et al 2018 ), while respiratory symptoms, including post-exercise cough following training and competition in cold climates are also commonly reported (Kennedy et al 2016 ; Kennedy and Faulhaber 2018 ; Sjöström et al 2019 ). Thus, asthmatic and non-asthmatic athletes alike could potentially benefit from preventive strategies to maintain normal respiratory function during exercise in sub-zero temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, short-duration, near-maximal exercise in cold environments and competition-like settings has been linked to a high incidence of EIB during screening of winter athletes (Heir and Larsen 1995 ; Wilber et al 2000 ; Kennedy et al 2019 ). Seasonal increases in airway inflammatory biomarkers have recently been highlighted in winter endurance athletes without asthma (Kennedy et al 2016 ; Kurowski et al 2018 ), while respiratory symptoms, including post-exercise cough following training and competition in cold climates are also commonly reported (Kennedy et al 2016 ; Kennedy and Faulhaber 2018 ; Sjöström et al 2019 ). Thus, asthmatic and non-asthmatic athletes alike could potentially benefit from preventive strategies to maintain normal respiratory function during exercise in sub-zero temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Finland show that up to 50% of the population report at least some cold-related symptoms (Harju et al, 2010 ; Näyhä et al, 2011 ) and that symptoms appear to be more common in women than men (Näyhä et al, 2011 ). A recent study found that experimental exposure to sub-zero temperatures at rest and when performing light exercise elicited 50 distinct symptoms among healthy subjects and patients with obstructive lung disease (Sjöström et al, 2019 ). Respiratory symptoms are also very common among children undertaking physical activity in cold temperatures (Rasi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each study subject was exposed on two separate occasions, at least one week apart. The environmental chamber is located at the Swedish Winter Sports Research Centre, Mid Sweden University, Östersund, and has been described elsewhere [ 34 ]. The study was carried out during April–June 2017, and the mean (range) outdoor temperature during the exposures was 8.3 (0.2–19.5) °C.…”
Section: Methodsmentioning
confidence: 99%
“…One questionnaire had previously been used in experimental exposure studies on air pollutants [ 38 ]. The other questionnaire was based on interviews during cold-exposure and simultaneous intermittent easy-moderate exercise for 1 h [ 34 ]. The symptoms inquired for in the questionnaires are presented in Table 2 and 4 Table 5 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation